Relative contribution of transport/surface flux to the seasonal vertical synoptic CO2 variability in the troposphere over Narita - Shamil Maksyutov; Yosuke Niwa; Yousuke Sawa; Hidekazu Matsueda; Toshinobu MacHida; Tomoko Shirai; Kaz Higuchi (Tellus: Series B, Chemical and Physical Meteorology, 2012)
Frequent CO2 measurements obtained by commercial aircraft provide a unique, quasi-continuous record of free-tropospheric CO2 variability. Vertically-resolved synoptic-scale fluctuations of CO2 over Narita International Airport (lat 35.8°N, 140.4°E, 43 m above sea-level) were investigated from November 2005 to March 2009, and combined with analyses of results from a transport model simulation for the year 2007 to retrieve information on sources contributing to the observed variability. The synoptic-scale variability of the observed CO2 mixing ratio, represented by the standard deviation (SD) from the fitted curves, increased in the upper troposphere in the spring, with a noticeable increase at all altitudes in the summer. This seasonal/altitudinal change of the observed SD was shown to be statistically significant throughout the observation period, and the model result agreed with the observation except for the underestimation of the summertime SD. Tagged simulations were conducted to evaluate the relative contribution of the regional fluxes to the synoptic-scale variability over Narita. The results indicate that the major contribution to the free troposphere (FT) variability was made by the fluxes in East Asia, while the Japanese fluxes contributed mostly to the variability in the planetary boundary layer (PBL). A sensitivity analysis was performed to evaluate the relative influence of transport and of flux magnitude on the CO2 SD over Narita for 2007. It was found that a change in the surface flux magnitude could affect the altitudinal distribution of the annual SD over Narita as follows: 41 and 3% at 9 km, 61 and 4% at 5 km, 19 and 83% at 0.5 km when the fossil fuel flux from East Asia and Japan was doubled, respectively. These results are qualitative in nature (since SD is a non-linear function of concentration and flux), but do indicate that the CO2 SD over Narita is more sensitive to the fluctuation in the atmospheric transport (synoptic-scale meteorological variability) in the FT, while showing much more sensitivity to the magnitude of local fluxes in the PBL. The results also point to the fact that vertical profiles of atmospheric CO2 variability at the synoptic scale could potentially provide a useful additional constraint in the inversion analysis of regional CO2 fluxes.